A clinical example of using a carbon-carbon composite to replace a femur diaphyseal defect - Chornyi, V. M.; Pertsov, V. I. (Zaporozhye Medical Journal, 2024)
A separate direction in osteosynthesis is the study on the possibilities of bone union after tumor resection. In this regard, the issue of using implants made of metals, polymers, and carbon, which have a high bone binding affinity, is on the agenda for modern oncological orthopedics. Studying carbon composite materials has shown practical effectiveness of their medical use, in particular in orthopedics and traumatology, that can be applied to replace bone defects in oncological traumatology. Aim. To determine the possibility of using carbon composite materials in the femur defect replacement after tumor resection. Clinical case. A case of using an implant made of the carbon composite material for a patient with right femur osteosarcoma and a pathological femoral middle-third fracture is presented. The study was carried out in accordance with the principles of the Declaration of Helsinki. The patient signed the written informed consent form for the study. Conclusions. The results of using the implant made of the carbon composite material have shown its permeability to X-rays and potential use for bone defect replacement in oncological traumatology.